Black sugarcane decoction reduces rat brain ischemia - Handayani, Ety Sari; Nugraha, Zainuri Sabta; Nurmasitoh, Titis; Kuswati, Kuswati; Ahsani, Dwi N.; Nanda, Ajeng G. (Universa Medicina, 2016)
BackgroundThere are people in Yogyakarta, who use black sugarcane decoction (BSD) to prevent stroke. BSD contains policosanol and antioxidants. It has been proven that policosanol can reduce global ischemia in Mongolian gerbils. This study aims to evaluate the effect of BSD on brain ischemia in a rat stroke model. MethodsA laboratory experiment using eighteen 3-month old male Wistar rats without any defects, of 175-250 g body weight. Brain ischemia was produced by a 20-minute bilateral carotid communis artery oclusion (BCCAO).  Using a rat stroke model, brain ischemia was produced by a 20-minute BCCAO. The rats were randomized into three groups: BSD treated stroke model rats (group 1), non treated stroke model rats (group 2), and sham operated rats (group 3). BSD was administered by gavage for 1 week before BCCAO. Decapitation of rats was performed two hours post BCCAO. Brain tissues were stained with 2,3,5-triphenyltetrazolium chloride (TTC). Ischemic areas were analyzed using Image J softwere. Statistical analysis was conducted by one way ANOVA test.ResultsThe mean percentages of rat brain ischemic area differed between group 3 (0.0 ± 0.0%), group 2 (3.13 ± 0.59%) and group 1 (1.15 ± 0.47%) p =0.001). Post hoc test showed that there was no difference between group 3 with group 1. Instead, there was a significant difference between  group 2 and the other groups.ConclusionThe administration of BSD reduced rat brain ischemia after bilateral carotid artery ligation.